Rejeição da medida provisória, conflito entre poderes e vácuo legislativo - Gouveia, Luiz Antonio Sampaio (2010)
The interim measure is an act of the Executive with force of law, by constitutional provision. Since ordinarily this legislative power has no jurisdiction to express and sometimes expresses dysfunctional abuse of the (Brazilian) President when it invades the jurisdiction of the Legislature, it confronts these powers. Within 120 days of its issue, if Congress does not appreciate it converting it into law, or rejects it, it loses its effectiveness with ex tunc effects. The legal relationship consummated under its support will be regulated by decree of the Legislature, issued within 60 days of these events. There will be legislative vacuum in fact, until the legislative decree is issued. Missing this, it will validate to the discipline of the legal relations it raised, causing questions about the constitutionality of this phenomenon. For this research, it was necessary literature on the subject that, in addition to numerous books, was marked by articles and journals, internet files and papers listed in the bibliography list of this work. After defining its juridical nature and studying its historical origins, with forays into the comparative Constitutional Law, claiming its constitutional condition, the clash of Power motivated by it is analyzed. A solution is proposed by concentrated control of constitutionality of the qualification requirements of provisional measures. It is impossible that void in law and claiming the unconstitutionality of co validation of provisional measures due to the lack of legislative decree, it is intended that these relations no longer depend on it and should be resolved by the judiciary